BIOFUEL CELLS - THE PROBLEMS AND PERSPECTIVES OF DEVELOPMENT. I. ENZIME FUEL CELLS - Є. В. Кузьмінський; П. I. Гвоздяк; Н. Б. Голуб (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2007)
In this rewiew the state of biofuel cells the problems concerning their development have been analyzed and determined. Biofuel cells are the electrochemical devices in which by the help of microorganisms the direct transformation of chemical energy of diggerent substances (carbohydrates, fats, proteins etc.) into electrical energy occurs as the result of biochemical transgormations.